Standar AAOIFI Dalam Harmonisasi Penyajian Laporan Keuangan Berbasis Syariah - Retnawati Siregar; Agus Agus; Saparuddin Siregar (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The importance of specific sharia-based accounting standards for regulating Islamic financial entities such as those issued by AAOIFI (Accounting and Auditing Organization for Islamic Financial Institutions) is still in doubt. The purpose of this research is to explore the reasons behind the formation of AAOIFI and provide data on how the harmonization of AAOIFI accounting standards in the reporting of sharia-based financial institutions. This research method uses library research and uses descriptive analysis. The findings indicate the need for the development of international guidelines and specific standards for Islamic Finance bodies in the IFRS scheme, as well as being a focus point on the standards set by AAOIFI. Therefore, there is a need for harmonization and compatibility between specific accounting standards for Islamic financial institutions and universally accepted and used accounting standards such as IFRS. Specific guidelines meant for IFIs would not be able to gain worldwide recognition without such collaboration.